Historically-cognitive stratum of ethnocultural lexis (on example of the Kazakh language) - Bissenbayeva, Meruyert; Osmanova, Zeinep; Tulegenova, Gaziza; Atabayeva, Mereke; Abisheva, Gulmira (Opción, 2019)
The purpose of the article is to show the ethno-cultural specificity of the Kazakh language in the world. Along with the methods of historico-comparative and traditional characteristics of the study of linguistic data, the following methods are used: a component-linguistic analysis, ethnolinguistic, semantic, etymological analyzes. As a result, Language through the word conveys all of the cultural wealth created by humankind: spiritual and material. In conclusion, the system of dialects and the meaning of words in accordance with the laws of development are subject to various semantic changes, and this is inherent in all stratums of the vocabulary of dialects.